2011
DOI: 10.1111/j.1399-0012.2011.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects on renal function of dose‐reduced calcineurin inhibitor and sirolimus in cardiac transplant patients

Abstract: One hundred and fifty-five patients (79 sirolimus and 76 controls) were included and had similar baseline characteristics. Sirolimus was started a mean of 1429 d post-CTX and maintained for a mean of 823 d. Reason for conversion to sirolimus was renal insufficiency (34%), vasculopathy (29%), recurrent rejection (19%), and other (18%). The eGFR was not different between groups at baseline (44.7 mL/min/1.73 m(2) vs. 46.0, p = 0.64) or at any point during follow-up: 90 d, 180 d, 1 yr, 2 yr, and 3 yr. conclusion: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In contrast to these reports, recent publications by Gonzalez-Vilchez et al 10 failed to report long-term improvement (28 months) of renal function in SIR-treated cardiac transplant recipients 9 ± 4 years following the procedure. Similar neutral observations were recently reported by Khandhar et al 11 These observations are also in agreement with the report from Gustafsson et al 39 In that study, a shorter time from transplantation to conversion was associated with a greater improvement in renal function at 6 months.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to these reports, recent publications by Gonzalez-Vilchez et al 10 failed to report long-term improvement (28 months) of renal function in SIR-treated cardiac transplant recipients 9 ± 4 years following the procedure. Similar neutral observations were recently reported by Khandhar et al 11 These observations are also in agreement with the report from Gustafsson et al 39 In that study, a shorter time from transplantation to conversion was associated with a greater improvement in renal function at 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…SIR therapy has also yielded increased triglyceride levels and proteinuria with limited change in blood pressure in most of the investigations. 8-12,29-34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial randomized trials by Eisen et al [54], and Keogh et al [55], indicated that EVL and SRL actually potentiate the nephrotoxic side effects of CNIs unless the doses of the CNIs are reduced. Several studies have, subsequently, studied HT patients in whom an m-TOR inhibitor has been introduced together with a CNI-reduction [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] or a CNI-withdrawal . Altogether, it appears as if both of the two strategies have beneficial effects on renal function, although questions remain regarding the safety and efficacy compared with ordinary CNI-therapy.…”
Section: Cni-minimizationmentioning
confidence: 99%